Depression, Executive Dysfunction, and Prior Economic and Social Vulnerability Associations in Incarcerated African American Men. (July 2018) - Scanlon, Faith A.; Scheidell, Joy D.; Cuddeback, Gary S.; Samuelsohn, Darcy; Wohl, David A.; Lejuez, Carl W.; Latimer, William W.; Khan, Maria R.
Low executive function (EF) and depression are each determinants of health. This study examined the synergy between deficits in EF (impaired cognitive flexibility; >75th percentile on the Wisconsin Card Sorting Test perseverative error score) and depressive symptoms (modified Centers for Epidemiologic Studies–Depression) and preincarceration well-being among incarcerated African American men ( N = 189). In adjusted analyses, having impaired EF and depression was strongly associated with pre-incarceration food insecurity (odds ratio [ OR ] = 3.81, 95% confidence interval [CI] = [1.35, 10.77]), homelessness ( OR = 3.00, 95% CI [1.02, 8.80]), concern about bills ( OR = 3.76, 95% CI [1.42, 9.95]), low significant other support ( OR = 4.63, 95% CI [1.62, 13.24]), low friend support ( OR = 3.47, 95% CI [1.30, 9.26]), relationship difficulties ( OR = 2.86, 95% CI [1.05, 7.80]), and binge drinking ( OR = 3.62, 95% CI [1.22, 10.80]). Prison-based programs to treat depression and improve problem-solving may improve postrelease success.